2004
DOI: 10.1063/1.1834989
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ordering in ilmenite-hematite bulk ceramics through proton irradiation

Abstract: We demonstrated the capability of MeV proton irradiation to promote chemical ordering processes in a solid at low temperature. We used the ilmenite–hematite solid solution system which allows estimation of the degree of ordering through measurement of its magnetization. Normally, ordering through diffusion would require high temperature annealing. At high temperatures, however, the equilibrium state would be less ordered and thus the achievable ordering incomplete. High energetic protons continuously transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The results have been published in [13][14][15]. These papers discuss in greater depth the various mechanisms through which radiation can interact with materials and change their basic properties.…”
Section: Non-linear I-v and Irradiationmentioning
confidence: 90%
See 2 more Smart Citations
“…The results have been published in [13][14][15]. These papers discuss in greater depth the various mechanisms through which radiation can interact with materials and change their basic properties.…”
Section: Non-linear I-v and Irradiationmentioning
confidence: 90%
“…This experiment was done at the Cyclotron Institute of Texas A&M University using the proton source of the following parameters: 10 and 40 MeV, total fluence=5× 10 10 p/cm 2 , and exposure time ranging from 10 min to 4 h. From these results we conclude that resistivity remains unchanged from proton irradiation. However, the chemical ordering takes place resulting in increase of magnetic moments for a whole range of IHC [14].…”
Section: Non-linear I-v and Irradiationmentioning
confidence: 98%
See 1 more Smart Citation
“…Radiation studies have shown that the magnetic properties are enhanced after irradiating these materials with protons while these properties remain unchanged after neutron irradiation. 9 They also have voltage-dependent resistivity, which makes them ideal materials for fabrication of varistors with low switching voltages and with applications in a radiation environment, for example space, nuclear reactors, etc. 10,11 Previously, thin films of IH using PLD were grown in vacuum and on sapphire substrates.…”
Section: Introductionmentioning
confidence: 99%
“…6 Both IHC33 and IHC45 are also excellent radhard materials. 6,[8][9][10][11] Therefore, the devices described here are expected to perform satisfactorily even when exposed to radiations such as in space. The non-linear I-V characteristics for a wide range of compositions for ceramic samples of IH with 0 < x < 0.45 is reported in reference .…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%